The practice of time management in construction projects - Lok, Siew Chin (2014)
The Malaysian construction industry plays a vital role in the country development. CIOB in 2008 has indicated that the quality of time-management on construction projects is generally poor. Therefore, an effective time management for the construction project is important in managing risk of delayed completion project. The aim of this project is to examine the practice of time management on construction project. The objectives of this study are to assess the respondents’ participation in the planning of construction works, to investigate how progress records are kept and to identify the process of monitoring the progress of work on construction industry. To achieve these objectives, there were thirty questionnaire survey distributed to the respondents. From the findings, project manager has the highest percentage in both drafting a planning method statement and project planning meetings. Most of the respondents had their experience of sequence was planned as a result of a discussion and written method statement, the activity durations being calculated in whole or in part, the price were allocated in separate documents with contingency, date constraints were used constraint the performance to dates given in the contract documents and float constraints were used to control critically. As for the progress reports, majority prefer to keep the records on paper but were immediately input into database. Most of them had the experience of additional work relation to labour allocation. When it came to relating the resource used to the work done and in which location, it was the experience of majority respondents identified task on schedule for both labour and plant and equipment records. The respondents preferred to report the progress in meeting or correspondence and the schedules were updated monthly. Lastly, most of them have corrected the logic to conform to progress achieved to deal with consequences of out of sequence work.